Comparison of the diagnostic accuracy of X-ray and computed tomography in patients with wrist injury. Issue 3 (March 2020) - Etli, Ibrahim; Kozaci, Nalan; Avci, Mustafa; Karakoyun, Omer Faruk
Highlights: XR is the first-choice imaging modality in the evaluation of wrist injuries. The sensitivity of XR is low for detecting carpal bone fractures, insertion joint fractures, and adjacent bone fracture. CT imaging should be preferred for diagnosis and treatment decision-making in complex or indistinct fractures. Abstract: Background: This study aimed to compare CT and XR images of patients admitted to the emergency department due to wrist injuries and to evaluate the accuracy of XR in the diagnosis of fractures. Methods: Patients; who admitted to ED with injuries due to wrist trauma and who underwent XR imaging and CT scans in the period from 1 January 2017 to 1 January 2018, were included in the study. CT scan image interpretation reports recorded in the hospital automation system were considered eligible to be included in the study. XR images were interpreted by an orthopedics and traumatology specialist. The sensitivity (Sn), specificity (Sp), positive predictive value (PPV), negative predictive value (NPV) and Kappa (κ) coefficient of XR were calculated according to CT. Inter-rater agreement was graded according to κ values. Results: A total of 274 patients were included in the study. Fractures were identified in the XR images in 180 (66%) patients and in the CT images in 196 (72%) patients. Compared to CT, the Sn, Sp, PPV, NPV and κ coefficient of XR were 89%, 92%, 97%, 77% and 0.764 respectively. Compared to CT, the highest sensitivity of XR was measured to detecting radius (Sn: 95%, κ: 0.896) and 5th metacarpal fractures (Sn: 77%, κ: 0.859), the lowest sensitivity of XR was calculated in detecting scaphoid, capitate, pisiform, trapezium hamate, and triquetrum fractures (Sn: 59–14%, κ: 0.619–0.240). The sensitivity and κ coefficient of XR were calculated 54% and 0.530 in the adjacent bone fracture, 83% and 0.830 in joint dislocation, 75% and 0.661 in the fractures extending to the joint space. Conclusions: XR is the first-choice imaging modality in the evaluation of wrist injuries, but CT imaging should be preferred when fractures extending to the joint space, adjacent bone fracture and carpal bone fracture are being considered.